IDEOLOGI MELUKAT DALAM PRAXIS KESEHATAN - Artana, I Wayan (Widya Duta: Jurnal Ilmiah Ilmu Agama dan Ilmu Sosial Budaya, 2018)
This article works through about ideology melukat and its role in patient doctor relationship. Ideology grasp is utilized in two different way. First, descriptive purification: as ? system thinks ?, ?trusty system ?, ?symbolic praktice? one is engaged social action and politics (neutral conception of ideology). Both of, mendasar's ala ideology is engaged process power relationship justification that asymmetric, in reference to justification process dominates (ideologies critical conception). Its quick is place growths melukat giving room managinging to get affix significant. Melukat also clear away doctor practice room as therapy of alternative complementary.